User awareness in the authenticity of mobile Quran apps - Talib, Shuhaili; Abubakar, Adamu; Mahmud, Murni (2016)
Reading Quran has been made easy with the advancement of Mobile Technology. People may have a digital copy of the Holy Quran on their mobile devices. They may read the Quran at their conveniences through smartphones and tablets. Many Mobile Quran Applications (Apps) are available to be downloaded and shared amongst users. However, not all developers of the apps inform the users on the originality and reliability of the Holy Quran contents. Furthermore, with the onward increasing number of such apps on the Internet, raised a question of users’ awareness on any means of authenticating the sources and contents. Thus, information on the usage and awareness of the authenticity of Quran Apps has been uncovered. Preliminary results of a quantitative survey of 34 respondents show 74% of them use Quran Apps and more than half, do not check the originality of the Quran contents. The results also show 56% of them are aware of the fake Quran Apps; however, 53% of the respondents indicate that they are unable to check the authenticity of the apps for various reasons. In terms of the method to check the Quran Apps, only 9% know how to find and navigate the apps for checking the authenticity. It is tentatively concluded that users require more awareness and guidance to ensure that they are reading and referencing to an authentic mobile copy of the Quran. This study leads to a future exploration of users’ behavior on awareness and navigational strategy for searching indicators of the authenticity of the Quran Apps.